Factors associated with loss of motivation and hesitation to work amongst frontline health care providers during the COVID-19 pandemic: A cross-sectional survey from a developing country. (November 2022) - Malik, Mehreen; Rehan, Syeda Tayyaba; Malik, Farheen; Ahmed, Jawad; Fatir, Chaudhary Abdul; Hussain, Hassan ul; Aman, Asiyah; Tahir, Muhammad Junaid
Abstract: Background: The COVID-19 took over the world in 2020 and a lockdown has been imposed seeing its fast spread. Frontline health care workers (HCWs) were reported frequently with a lack of motivation, hesitancy and unwillingness to perform their duties during this pandemic. This cross-sectional survey aims to evaluate the factors associated with lack of motivation and increased hesitancy among the frontline HCWs to perform their duties during COVID-19 pandemic. Materials and methods: A total of 239 HCWs were included in this web-based cross-sectional study, who have worked during the COVID-19 pandemic. The anonymous online questionnaire was sent to all faculty, trainees and staff of Aga Khan University Hospital in Karachi, Pakistan. The survey was conducted from September 2020 to January 2021 during the COVID-19 pandemic. All data was exported into Statistical Package for Social Sciences Version 19 for multivariate analysis. Results: The risk of getting infected was strongly reported by 180 participants, and it was associated with higher hesitation to work (aOR = 6.09 [2.55–14.59]). Fifty-one participants felt that lack of knowledge about prevention and protection was associated with lower motivation to work (aOR = 0.66 [0.35–1.25]). Participants reported higher hesitation due to the burden of changed quality of work, physical exhaustion, mental exhaustion and altered sleep patterns. Sense of feeling protected by their hospitals was a motivating factor, and participants receiving adequate support reported higher motivation to work (aOR = 2.60 [1.32–5.14]). Conclusion: Fear of infection, increased working hours, and inadequate support of the workplace played a key role in escalating the hesitancy among HCWs to perform their duties. Lack of disease knowledge and paucity of personal protective equipment further lowered the motivation levels of HCWs to work effectively during the COVID-19 pandemic. Highlights: The COVID-19 took over the world in 2020 and a lockdown has been imposed seeing its fast spread. Frontline health care workers (HCWs) were reported frequently with a lack of motivation, hesitancy and unwillingness to perform their duties during this pandemic. This cross-sectional survey aims to evaluate the factors associated with lack of motivation and increased hesitancy among the frontline HCWs to perform their duties during COVID-19 pandemic. Fear of infection, increased working hours, and inadequate support of the workplace played a key role in escalating the hesitancy among HCWs to perform their duties.